Vestibular-evoked myogenic potentials in patients with large vestibular aqueduct syndrome. (2nd January 2020) - Zhang, Yan; Chen, Zichen; Zhang, Yuzhong; Hu, Juan; Wang, Junli; Xu, Min; Zhang, Qing
Abstract: Background: The vestibular function in patients of large vestibular aqueduct syndrome (LVAS) has not been clarified yet. Aims/objectives: To investigate the characteristic of otolithic organ in LVAS patients, we accessed their ocular and cervical vestibular evoked myogenic potentials (oVEMPs and cVEMPs). Material and methods: This study was carried out between 29 bilateral LVAS patients and 35 healthy controls. Parameters of VEMPs were analyzed. Result: In children patients, response rate for oVEMP was 93.47% and 86.95% for cVEMP. No statistical significance was found compared to their controls. In adult patients, response rate for oVEMP was 83.33% and 75% for cVEMP, which were statistically lower than their controls. In comparison to parameters of VEMPs, no statistical significance were found in children group. Amplitude of oVEMP was significantly higher and that of cVEMP was lower in LVAS adults. N1 latencies were significantly longer and P1 latencies were shorter in adult patients than in controls of cVEMP. Thresholds and N1-P1 intervals of VEMP were found no statistical significance in adult group. Conclusions and significance: We discovered a severer otolithic dysfunction in adults than in children patients. We recommend cVEMP a more effective and sensitive method than oVEMP in assessment of LAVS adult patients.